Controlled formation of large-area single-crystalline TIPS-pentacene arrays through superhydrophobic micropillar flow-coating. Issue 10 (1st March 2017) - Xiao, Chengyi; Kan, Xiaonan; Liu, Chunming; Jiang, Wei; Zhao, Guangyao; Zhao, Qiang; Zhang, Lei; Hu, Wenping; Wang, Zhaohui; Jiang, Lei
Abstract : Single crystalline arrays with an area of 1 × 2 cm 2 and high mobilities could be obtained through the superhydrophobic micropillar flow-coating (SMFC) technique. Abstract : A convenient and controlled organic semiconductor alignment strategy, superhydrophobic micropillar flow-coating (SMFC), is presented. Patterned, large-area (>1 cm 2 ) 6, 13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene) single-crystalline arrays which show hole mobilities up to 6.8 cm 2 V −1 s −1 were obtained via this method. Crucially, the polymorphism of TIPS-pentacene was regulated by tuning the flow rate, solvent and the substrate hydrophobicity. These results indicate that this technique is reliable for creating uniform and homogenous organic single-crystalline arrays with controlled crystal packing, thickness, and position.